PENGARUH PEMBERIAN PUPUK PETROGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH (Capsicum annum L.) - Josina Irene Brigetha Hutubessy (AGRICA, 2014)
This study aims at finding out the Petragonik fertilizer’s dose on the growth and yield of red chilli and finding out the optimum dose of Petragonik fertilizer that can optimize the growth and yield of red chilli. This study employed group random design with the treatment of Petragonik fertilizer (P0) or control, (P1) 150 kg/ha-1or (75g petak1), (P2) 300 kg/ha-1or 150 g petak1), (P3) 450kg/ha-1or (225 g petak1 , (P4) 600 kg/ha-1or ( 300 g petak-1). The findings reveal that 450 kg/ha of fertilizer dose has a very significant influence on the height of plants (49,91cm) or increasing to (6,9%), a number of leaves (25 sheets) or rising to (10,07%), and wide of leaves (315 cm²) or a rise of (7,9%) and the yields of tan-1 (28,33 fruits), the diameter of chilli (3,50mm), the weight of fresh chilli ha-1 (416,83) and harvest index of (12,89%).